Intralesional 8.33% Rifamycin infiltration; New treatment for cutaneous leishmaniasis - Nameer K. Al-Sudany; Yousif J. Ali (Wolters Kluwer Medknow Publications, 2016)
Background: Cutaneous leishmaniasis (CL) is an endemic disease in Iraq, for which many therapies had been tried, aiming to induce cure with no or minimal scaring. Rifamycin is an antibacterial agent, with the ability to inhibit bacterial DNA-dependent RNA synthesis and it is effective against extra- and intracellular microorganisms. Objective: To evaluate the effectiveness and safety of intralesional 8.33% Rifamycin infiltration in treatment of cutaneous leishmaniasis. Patients and methods: This is an open controlled therapeutic trial, carried out in the outpatient clinic of Dermatology & Venereology, Al-Yarmouk Teaching Hospital during the period between the first of December 2013 to the end of June 2014. A total of 29 patients have been enrolled in this therapeutic trial, however 4 patients were defaulted and 25 patients have completed the therapeutic trial. Fourteen (56%) were males and 11 (44%) were females, with a male to female ratio 1.27. Their ages ranged from 6 to 60 years, with a mean ± SD of 28.6 ± 14.9 years. The total number of lesions was 56 and the duration of lesions ranged between 4 and 18 weeks with a mean ± SD of 9.9 ± 4.4 weeks. The size of lesions ranged from 0.5 to 6 cm in diameter with a mean ± SD of 2.46 ± 1.17 cm. All patients have been diagnosed through history and clinical examination and the diagnosis was confirmed by skin smear and biopsy. The lesions were divided into two groups; group A treated with intralesional 8.33% Rifamycin infiltration every 2 weeks for a maximum of 5 sessions, while group B was left untreated as a control group. Follow up was every 2 weeks during the treatment period, and for 6 weeks after completing the therapeutic sessions. Results: Twenty five patients with a total of 56 lesions were completed the study period. Twenty one (37%) lesions were ulcerative and 35 (63%) were non ulcerative lesions. Ten (40%) patients had single lesion whereas 15 (60%) patients had multiple lesions. In group A, 38 (92.7%) out of 41 lesions showed a cure with 2-5 sessions with a mean ± SD of 4.9 ± 0.79 sessions, while in the control group no lesion had significantly improved or cured. At the end of the study period, only 8 out of 41 treated lesions have left trivial scars. Most of the lesions showed transient hyperpigmentation at the end of the study, but fortunately, it had disappeared in all cases few weeks later. Conclusion: Rifamycin 8.33% solution given intralesionally in cutaneous leishmaniasis is a highly effective agent with a success rate of 92.7%. For cure, it needs 2-5 local infiltrations given every two weeks. In addition to being effective, it is a safe, and less costly therapeutic option for cutaneous leishmaniasis.